Decline or renewal? Factors influencing the evolution of mature industrial clusters - Tobias König; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2024)
The evolution of industrial clusters has received much attention in the recent literature on evolutionary economic geography (EEG) and regional science. However, scientific results on the influence of different factors on the decline or renewal of mature industrial clusters are scarce. Therefore, this study identifies different factors: preconditions, triggering events and self-augmenting processes, and examines their influence on declining or renewing industrial clusters. In order to obtain transferable results, this meta-analysis is based on 69 individual empirical case studies from different countries and industries. The empirical results show, firstly, that the decline and renewal of industrial clusters is driven by different preconditions, triggering events and self-augmenting processes. Secondly, these factors change over time and may have both positive and negative dimensions. Finally, the decline of industrial clusters is more often associated with unfavorable preconditions and triggering events, while self- augmenting processes are more often found in the context of cluster renewal.
Keywords: O33; R10; R11; 330; Cluster; Evolution; Decline; Renewal; Meta-analysis